(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
this paper focuses on the role of intangible elements of the public spaces in the residential areas such as a neighbourhood. The main emphasis is the significance of the factor of social satisfactions on developing public spaces. The research to date has tended to focus on examining the physical quality of public space, particularly tangible features, but fewer have dealt with the intangible features that related to the residents’ social life and community interaction. Consequently, in this research, the analysis includes some important intangible elements such as a sense of community, social satisfaction and safety and security in the public spaces and the local initiatives. The research includes two case studies in Misurata, Libya. Both cases are neighbourhoods type with similar in size, population, number of houses and distance from the city centre. However, one case is a Governmental Neighbourhood GNs while the other one is a Traditional Neighbourhood TNs. This inquiry is a qualitative research, however, it adopted mixed methods approach, and i.e. both questionnaires and in-depth interviews were utilized for data collection. The results of this study show that there are a several crucial findings related to the importance of these intangible elements, these findings suggest some practical guidelines to be considered in new development projects.